Serum proteins reflecting inflammation, injury and repair as biomarkers of disease activity in ANCA-associated vasculitis. Issue 8 (12th September 2012) - Monach, Paul A; Warner, Roscoe L; Tomasson, Gunnar; Specks, Ulrich; Stone, John H; Ding, Linna; Fervenza, Fernando C; Fessler, Barri J; Hoffman, Gary S; Iklé, David; Kallenberg, Cees GM; Krischer, Jeffrey; et al.
Abstract : Objective: To identify circulating proteins that distinguish between active anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and remission in a manner complementary to markers of systemic inflammation. Methods: Twenty-eight serum proteins representing diverse aspects of the biology of AAV were measured before and 6 months after treatment in a large clinical trial of AAV. Subjects (n=186) enrolled in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial were studied. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels were available for comparison. The primary outcome was the ability of markers to distinguish severe AAV (Birmingham Vasculitis Activity Score for Wegener's granulomatosis (BVAS/WG)≥3 at screening) from remission (BVAS/WG=0 at month 6), using areas under receiver operating characteristic (ROC) curve (AUC). Results: All subjects had severe active vasculitis (median BVAS/WG=8) at screening. In the 137 subjects in remission at month 6, 24 of the 28 markers showed significant declines. ROC analysis indicated that levels of CXCL13 (BCA-1), matrix metalloproteinase-3 (MMP-3) and tissue inhibitor of metalloproteinases-1 (TIMP-1) best discriminated active AAV from remission (AUC>0.8) and from healthy controls (AUC>0.9). Correlations among these markers and with ESR or CRP were low. Conclusions: Many markers are elevated in severe active AAV and decline with treatment, but CXCL13, MMP-3 and TIMP-1 distinguish active AAV from remission better than the other markers studied, including ESR and CRP. These proteins are particularly promising candidates for future studies to address unmet needs in the assessment of patients with AAV.